The Great Smelling Bee : Rotten School #2 - Stine, R. L., 1943-; Park, Trip (Edina, Minn. : Spotlight, 2011)
In order to hide a bulldog in his no-pets-allowed dorm, scheming fourth-grader Bernie Bridges enrolls his pet as a transfer student.
Originally published: New York : HarperCollins, c2005.
"A Parachute Press book."
Keywords: Boarding schools -- Fiction; Schools -- Fiction; Bulldog -- Fiction; Dogs -- Fiction; Pets -- Fiction; Private schools -- Fiction; Bulldogs -- Fiction; Dogs -- Fiction; Pets -- Fiction; School stories